2018
DOI: 10.1002/jclp.22612
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic distress: A review and synthesis of 15 years of research

Abstract: Peritraumatic distress is associated with PTSD symptom severity, other psychiatric symptoms, and severity of PTSD-related symptoms after exposure to non-Criterion A events, suggesting that peritraumatic distress is a risk factor for various psychiatric outcomes and furthering our understanding of the impact of subjective experience on trauma psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 88 publications
4
54
1
2
Order By: Relevance
“…Conversely, in the regression analysis financial difficulties and anxiety symptoms were associated with PTSS. In particular, a great amount of research reported that anxiety, fear, and distress at the time of the trauma were strictly associated with the development of post-traumatic stress reactions (55). Comorbid anxiety was related to an increased risk of PTSD onset both in general population and in longitudinal studies on BD patients (51,52,56).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the regression analysis financial difficulties and anxiety symptoms were associated with PTSS. In particular, a great amount of research reported that anxiety, fear, and distress at the time of the trauma were strictly associated with the development of post-traumatic stress reactions (55). Comorbid anxiety was related to an increased risk of PTSD onset both in general population and in longitudinal studies on BD patients (51,52,56).…”
Section: Discussionmentioning
confidence: 99%
“…Although most individuals prove to be resilient after being exposed to a traumatic event ( Bonanno et al., 2007 ), several risk factors may compromise the effectiveness of adaptation, including prior psychiatric history, female sex, lack of social support ( Brewin et al., 1999 ; Ozer et al., 2003 ; Carmassi et al., 2020a , 2020b ), having young children ( Yehuda et al., 2015 ; Bryant 2019 ); experiencing feelings of helplessness during the trauma or intensity of emotions when exposed (i.e., anger, peritraumatic distress) ( Vance et al., 2018 ; Carmassi et al., 2017 ). On the other hand, resilience, defined as the capacity to react to stress in a healthy way through which goals are achieved at a minimal psychological and physical cost ( Epstein and Krasner, 2013 ), plays a key role in mitigating the impact of traumatic events and hence reducing PTSS, enhancing at the same time the quality of care ( Wrenn et al., 2011 ; Ager et al., 2012 ; Haber et al., 2013 ; McGarry et al., 2013 ; Craun and Bourke, 2014 ; Hamid and Musa, 2017 ; Colville et al., 2017 ; Cleary et al., 2018 ; Winkel et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…from one another (Massazza et al, 2020), they tend to be associated with higher levels of post-trauma psychopathology, most commonly PTSD (Vance et al, 2018), but also depression (Bunnell et al, 2018).…”
mentioning
confidence: 99%